Antimicrobial Sensitivity of Neonatal Bacterial Sepsis - Iswandari, Nadya; Primadi, Aris; Sudigdoadi, Sunarjati (Althea Medical Journal, 2017)
Background: Appropriate treatment on neonatal bacterial sepsis is important based on the exact etiology to prevent bacterial resistance, but bacterial identification using blood cultures requires a considerable time. The newest data of various bacteria and their sensitivity can be used to assist empirical antibiotics usage. This study was conducted to identify bacterial profile that caused neonatal sepsis and their sensitivity to antibiotics at Dr. Hasan Sadikin General Hospital Bandung..Methods: A total of 275 neonatal sepsis cases and 288 blood cultures results were collected from a database provided by Dr. Hasan Sadikin General Hospital Bandung during the period of July 2011 toDecember 2012 (three semesters).Â Etiology of the bacteria and antimicrobial sensitivity profile data were taken from positive bacteria results. Then, these variables were processed using the descriptive method and classified by semesterResult: The most common bacteria that caused neonatal sepsis in the second semester 2011 is Serratia marescens, the first semester 2012 was Enterobacter aerogenes and in the second semester 2012 was Burkholderia cepacia. The most sensitive antibiotics were piperacillin tazobactam, cefepime, meropenem and amikacin in all three semesters, gentamycin in the second semester 2011 and 2012, and amoxicillin clavulanic in the second semester 2012.Conclusions: Bacterial and antimicrobial sensitivity profile is varied in every semester.Keywords: Antimicrobial sensitivity profile, bacterial profile, neonatal sepsisDOI:Â 10.15850/amj.v4n2.1072